Advances on the use of diazonium chemistry for functionalization of materials used in energy storage systems. (October 2015) - Assresahegn, Birhanu Desalegn; Brousse, Thierry; Bélanger, Daniel
Abstract: Even if energy storage technologies such as batteries and electrochemical capacitors are currently widely used, their performance is still insufficient for some applications. A key component of these systems is the electrode and recent research works focused on the improvement of its stability, safety, performance and cost-effectiveness. Among the approaches being investigated, the chemical modification of the electrode material is very attractive. Covalent grafting of different organic moieties using diazonium chemistry is becoming a popular method for the modification of electrode materials. In this short review, basic information related to the synthesis of diazonium salt is given together with detailed mechanisms, characterization techniques and methods used for the chemical functionalization of the different electrode materials. Special emphasis is also given on the spontaneous covalent attachment of organic molecules by reduction of diazonium ions on surfaces as it provides a convenient way to scale-up for industrial productions. Moreover, recent advances on the use and contribution of the grafted molecules in enhancing the performance of electrochemical capacitor and lithium-ion batteries are presented.